DNAJC proteins and pathways to parkinsonism. (20th June 2019) - Roosen, Dorien A.; Blauwendraat, Cornelis; Cookson, Mark R.; Lewis, Patrick A.
Abstract : The DNAJC protein family is a subclass of heat shock proteins that has attracted recent attention due to the identification of mutations that are linked with parkinsonism, a feature of Parkinson's disease and other neurological disorders. In this review, we discuss the current genetic and functional evidence of the association of these DNAJC proteins with disease and how mutations in these proteins may contribute to disease pathogenesis. Although DNAJC6 (Auxilin), DNAJC12, and DNAJC5 (CSPα) exhibit strong genetic association with disease, DNAJC26 (GAK), DNAJC13 (RME‐8), and DNAJC10 (Erdj5) require additional evidence to definitively link reported variants to parkinsonism. Remarkably, multiple DNAJC proteins (Auxilin, GAK, RME‐8, CSPα) functionally converge on pathways of synaptic trafficking and clathrin dynamics, highlighting an important role of those pathways in the pathogenesis of parkinsonism. Further research is required to define the mechanisms through which these mutations contribute to disease etiology. Abstract : A number of DNAJC proteins have been recently linked to risk of Parkinson's disease, uncovering a potential new pathway resulting in neurodegeneration. In this review, the evidence linking DNAJC proteins to parkinsonism is summarized, with potential mechanisms connecting these proteins to neuronal cell death discussed. (Images adapted from An Essay on the Shaking Palsy, J. Parkinson, 1817, and Manual of the Diseases of the Nervous System, W. Gower, 1886; clathrin cage derived from PDB1XI5 ).